In vitro antioxidant and anti-inflammatory activities of selected polyherbal formulations sold in Nigeria - Odangowei Inetiminebi Ogidi (Shahrekord University of Medical Sciences, 2024)
Background and aims: Nonsteroidal anti-inflammatory drugs (NSAIDs) or corticosteroid analgesics are recommended to alleviate or reduce pain. Regrettably, many of these drugs may induce bleeding, dyspepsia, cardiac complications, renal issues, and various short- or long-term adverse effects. Consequently, there has been an escalation in the endeavor to develop natural anti-inflammatory medications, driven by the growing number of individuals seeking natural therapies to manage their pain. The polyherbal formulations (Yoyo and Dr. Iguedo Goko bitters) have not assessed their antioxidant and anti-inflammatory activities; hence, this study "in vitro antioxidant and anti-inflammatory activities of selected polyherbal formulations sold in Nigeria." Methods: The evaluation of antioxidant activity was performed using three assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals, hydrogen peroxide (H2 O2 ) scavenging activity, and ferric reducing antioxidant power. In vitro, anti-inflammatory efficacy was investigated using the human red blood cell (HRBC) membrane stabilization technique. Results: The DPPH radical scavenging ability result was observed; the IC50 value of Yoyo bitters (40.63±0.90 % at 250 µg/mL) was highest, while Dr. Goko bitters (3.26±0.21% at 50 µg/mL) was lowest. Meanwhile, the positive control (ascorbic acid) had an IC50 value of 93.54±0.57% at 250 µg/mL. The ferric-reducing antioxidant power of the samples was highest in Dr. Goko bitters, 1.96±0.02 % at 250 µg/mL, and lowest in Dr. Goko and Yoyo bitters, 0.46±0.01% at 100 and 50 µg/mL, respectively. The hydrogen peroxide free radical scavenging activity of the samples was highest in Yoyo bitters, 58.0.3±0.60 % at 250 µg/mL, and lowest in Dr. Goko bitters, 7.28±0.02 % at 50 µg/mL. The anti-inflammatory findings indicate that Yoyo bitters exhibited the highest percentage protection (89.46±6.11%) at a concentration of 1000 μg/mL, while the lowest percentage protection (26.62±1.13%) was observed at a concentration of 200 μg/mL. The reference standard diclofenac sodium has a percentage of 90.46±1.44 at a concentration of 1000 μg/mL. Meanwhile, the poly-herbal formulations had the highest and lowest total phenolic concentrations in Yoyo bitters (97.52±1.43 mg GAE/g at 250 µg/mL), and Dr. Goko bitters (47.3±1.44 mg GAE/g at 50 µg/mL), respectively. Conclusion: The findings suggest that the formulations might not have effective antioxidant and anti-inflammatory activities when compared with the reference standard drugs (ascorbic acid and diclofenac sodium), respectively.